2018
DOI: 10.1111/febs.14428
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of potassium activation in plant asparaginases

Abstract: l-asparaginases (EC 3.5.1.1) play an important role in nitrogen mobilization in plants. Here, we investigated the biochemical and biophysical properties of potassium-dependent (PvAspG1) and potassium-independent (PvAspG-T2) l-asparaginases from Phaseolus vulgaris. Our previous studies revealed that PvAspG1 requires potassium for catalytic activation and its crystal structure suggested that Ser-118 in the activation loop plays a critical role in coordinating the metal cation. This amino acid residue is replaced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Before genetic transformation, these analyses were performed to ensure the proper conformation and folding of targeted protein. From homology modelling we can infers that the ZmASN protein has close resemblance to the human threonine aspartase (2a8i) while the presence of conserved residues of PDB ID:2gez (potassium-independent plant asparaginase) in the active site of the ZmASN protein confirmed that it is the K + -independent asparaginase with Thr267 as its nucleophile, which is in accordance with the study by 2,35 where Thr293 was the nucleophile. The ZmASN possess K + -independent L-asparaginase activity as determined by in silico analysis whereas due to its structural similarity to 2a8i (human taspase1) it may also possess isoaspartyl aminopeptidase activity.…”
Section: Phenotypic Analysis Of Transgenic Cotton Lines Though the Esupporting
confidence: 87%
“…Before genetic transformation, these analyses were performed to ensure the proper conformation and folding of targeted protein. From homology modelling we can infers that the ZmASN protein has close resemblance to the human threonine aspartase (2a8i) while the presence of conserved residues of PDB ID:2gez (potassium-independent plant asparaginase) in the active site of the ZmASN protein confirmed that it is the K + -independent asparaginase with Thr267 as its nucleophile, which is in accordance with the study by 2,35 where Thr293 was the nucleophile. The ZmASN possess K + -independent L-asparaginase activity as determined by in silico analysis whereas due to its structural similarity to 2a8i (human taspase1) it may also possess isoaspartyl aminopeptidase activity.…”
Section: Phenotypic Analysis Of Transgenic Cotton Lines Though the Esupporting
confidence: 87%
“…The random mutagenesis of the EcAIII protein presented in this work is the first attempt to investigate how well the prototypic Ntn-hydrolase can tolerate multiple simultaneous substitutions in the active site. Some single site-directed mutagenesis experiments have been performed previously for similar enzymes to elucidate the catalytic and autoproteolytic mechanisms (Nomme et al, 2014;Michalska et al, 2008;Ajewole et al, 2018). Our sequencing analysis showed that the frequencies of residues at selected mutation sites are not uniform, but this is a typical result of local randomization with the use of degenerate codons (Tang et al, 2012).…”
Section: Lesson 1: the Entire Ecaiii Fold Adapts Well To New Substitu...mentioning
confidence: 82%
“…Ser is replaced by isoleucine, the enzyme loses its potassium dependence. Conversely, introduction of serine at the corresponding position in the potassium-independent enzyme from P. vulgaris endowed it with potassium sensitivity (Ajewole et al, 2018). Interestingly, it was also discovered that in the crystal structure of the D90E active-site mutant of the Class 1 EcAII enzyme there is a conserved zinc-binding site formed by Asp100, His197 and Asp200 (Borek et al, 2014; Supplementary Fig.…”
Section: Regulation Of the Enzymatic Activity: Metal-binding Loops And Catalytic Switchmentioning
confidence: 99%